Analysis of Job Satisfaction Levels Among Islamic Religious Education Teachers in Kabupaten Agam - Nurul Mawaddah Al-Mursal; Zulfani Sesmiarni (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze the level of job satisfaction among Islamic Education (PAI) teachers in Agam Regency, West Sumatra, Indonesia. Employing a quantitative descriptive approach, data were collected through structured questionnaires administered to 138 PAI teachers across various educational levels. The descriptive analysis revealed a generally high level of job satisfaction, with 51.4% of respondents categorized as